Animal models of erectile dysfunction - Gajbhiye, Snehlata V. (Indian J Urol, 2015)
Animal models have contributed to a great extent to understanding and advancement in the field of sexual medicine. Many current medical and surgical therapies in sexual medicine have been tried based on these animal models. Extensive literature search revealed that the compiled information is limited. In this review, we describe various experimental models of erectile dysfunction (ED) encompassing their procedures, variables of assessment, advantages and disadvantages. The search strategy consisted of review of PubMed based articles. We included original research work and certain review articles available in PubMed database. The search terms used were “ED and experimental models,” “ED and nervous stimulation,” “ED and cavernous nerve stimulation,” “ED and central stimulation,” “ED and diabetes mellitus,” “ED and ageing,” “ED and hypercholesteremia,” “ED and Peyronie's disease,” “radiation induced ED,” “telemetric recording,” “ED and mating test” and “ED and non-contact erection test.”